INFORMATION BASIS FOR THE ASSESSMENT OF THE EQUITY CAPITAL OF ECONOMIC ENTITIES IN UZBEKISTAN - Yuldasheva D. A. (World Scientific Research Journal, 2025)
Annotation.    In modern market conditions, the main successful operation of the enterprise is economic stability. When an enterprise is economically stable, it has a number of advantages over other companies in the same field in terms of loans and investments, in the selection of suppliers and qualified personnel. The higher financial stability of the enterprise makes it more autonomous from unforeseen changes in market conditions and leads to a reduction in the risk of bankruptcy. The lack of economic stability can lead to the insolvency of enterprises, lack of funds to finance current and investment activities, and bankruptcy with a deterioration in financial condition.